2022
DOI: 10.3233/jad-215117
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Costs of Paid and Unpaid Care for People with Dementia: Longitudinal Findings from the IDEAL Cohort

Abstract: Background: The drivers of costs of care for people with dementia are not well understood and little is known on the costs of care for those with rarer dementias. Objective: To characterize use and costs of paid and unpaid care over time in a cohort of people with dementia living in Britain. To explore the relationship between cohort members’ demographic and clinical characteristics and service costs. Methods: We calculated costs of health and social services, unpaid care, and out-of-pocket expenditure for peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…Confirmation with medical records was not possible to determine accuracy of this information. Issues around accuracy of self‐reporting have been discussed in a previous paper, 54 with literature indicating that under‐reporting is more common than over‐reporting when compared to medical records 55,56 . The self‐reported number of symptoms in these cases are low, and any impact of self‐reporting on results is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Confirmation with medical records was not possible to determine accuracy of this information. Issues around accuracy of self‐reporting have been discussed in a previous paper, 54 with literature indicating that under‐reporting is more common than over‐reporting when compared to medical records 55,56 . The self‐reported number of symptoms in these cases are low, and any impact of self‐reporting on results is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Confirmation with medical records was not possible to determine accuracy of this information. Issues around accuracy of self-reporting have been discussed in a previous paper, 54 with…”
Section: Limitationsmentioning
confidence: 99%
“…The present systematic review aimed to provide an updated and comprehensive overview of the efficacy of non-pharmacological treatments in patients with LBD. Although LBD is the second most common neurodegenerative dementia after Alzheimer’s disease and causes a substantial social impact [6, 40], definitive clinical guidelines are still lacking. Previous systematic reviews on non-pharmacological interventions in people with LBD reported PT interventions [8] or other various evidence-based or non-evidence-based interventions, such as occupational therapy, psychoeducational therapy, music therapy [9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…This may be because people with PDD and DLB have poorer QoL and ‘living well’ scores – as do their carers – compared to people with AD, VaD and FTD 32 . Movement disabilities associated with PDD and DLB may also be more likely to require specialised symptom management than difficulties associated with AD, therefore resulting in more frequent provision of support services 33 . Moreover, people with PDD may have received support from specialist Parkinson's disease services prior to developing dementia, which may improve subsequent receipt of support compared to people with AD, for whom support may be more limited.…”
Section: Discussionmentioning
confidence: 99%